The influence of personality on students' career decisiveness: A comparison between Chinese and German economics and management students - Marjaana Gunkel; Christopher Schlaegel (Management Revue, 2010)
Within the last decade, the relation between personality and career decisiveness has received increased attention. This study examines the country-specific influence of the Big Five personality traits on career decisiveness and its determinants, namely career related adaptability, career-related optimism, and career-related knowledge, among 406 Chinese and German economics and management students. The results show that personality traits affect career decisiveness and its determinants and that the effects partly differ across countries. The findings, their implications, and further research directions are discussed and suggestions for career counseling are made.
Keywords: 650; career decisiveness; country comparison; personality traits